Psychosocial and psycho-political predictors of social inequality justification - Gatica, Lucas (2017)
The objective of the study was to determine the predictive power of certain ideological (right-wing authoritarianism, belief in a just world, social dominance orientation, ideo logical self-positioning), cognitive (causal attributions of poverty and prejudice against poor people) and socio-demographic variables on the justification of social inequality. A correlational design was employed. Participants were 305 male and female students from the National University of Cordoba, Argentina ages 18-60 (M=22.95; SD=4.75). Results indicate particularities of the predictive power of these variables depending on the evaluated dimension of the justification of social inequality. Based on these results, the contribution of political psychology to the understanding of the psychosocial mechanisms that enable the legitimation of unequal situations is discussed.